2020
DOI: 10.1103/physrevd.102.035018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the early kinetic decoupling in a fermionic dark matter model

Abstract: We study the effect of the early kinetic decoupling in a model of fermionic dark matter (DM) that interacts with the standard model particles only by exchanging the Higgs boson. There are two DM-Higgs couplings, namely CP-conserving and CP-violating couplings. If the mass of the DM is slightly below half of the Higgs boson mass, then the couplings are suppressed to obtain the measured value of the DM energy density by the freeze-out mechanism. In addition, the scattering processes of DM off particles in the th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…In fact, it has repeatedly been pointed out that chemical and kinetic decoupling can be intertwined in a way that significantly affects the result of relic density calculations [24][25][26][27][28][29][30][31][32][71][72][73][74][75]. To provide context, we have therefore devoted a large part of this article (Sect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it has repeatedly been pointed out that chemical and kinetic decoupling can be intertwined in a way that significantly affects the result of relic density calculations [24][25][26][27][28][29][30][31][32][71][72][73][74][75]. To provide context, we have therefore devoted a large part of this article (Sect.…”
Section: Discussionmentioning
confidence: 99%
“…For Scalar Singlet masses slightly smaller than half of the Higgs mass it was found that a larger coupling to the Higgs is required to obtain the right relic abundance, which interestingly implies that future measurements of the Higgs-to-invisible decay width can probe more of the parameter region than expected from the standard relic abundance computation, see Refs. [25,29,51] for experimental probes and also for other Higgs resonance scenarios with similar effects.…”
Section: Resonant Annihilationmentioning
confidence: 98%
See 1 more Smart Citation
“…If the dark matter is a thermal relic, then the present-day dark matter abundance, Ω χ h 2 = 0.11, sets the annihilation cross section at the time of freeze-out, which is the well-known O(1) pb weak-scale cross section [56][57][58][59][60][61][62][63][64][65][66][67]. Recent work [68,69] has shown that for models with a hierarchy between annihilation and scattering strengths, early kinetic decoupling before freeze-out alters this number, requiring a larger cross section to achieve the observed abundance. At most extreme, a ∼ 20 pb annihilation cross section may be needed for a ∼ 57 GeV dark matter with purely imaginary couplings, though this is quite sensitive to the details of the QCD phase transition.…”
Section: Annihilationmentioning
confidence: 99%
“…We comment on the allowed parameter space m χ m h i /2. For more precise calculations in the region m χ m h i /2, the effect of the early kinetic decoupling from the SM thermal bath should be taken into account [73,74]. If this effect is included, one can expect that the red line in Fig.…”
Section: Long-lived Pngb As Dm Candidatementioning
confidence: 99%